Considerations for a Stronger First Mover Advantage Theory - Suarez, Fernando F.; Lanzolla, Gianvito (Academy of Management Review, 2008)
In this article the authors answer a critique, published elsewhere in the magazine, of their article "The Role of Environmental Dynamics in Building a First Mover Advantage Theory." They claim that the criticism of their business theory was not valid on the grounds that the critics did not have a firm grasp of the business literature and concepts on which original article was based. They reject the notion posited by the critics that new product management is a function of strategic choice. Aspects of their research and methodology are discussed.